Dr. Tony Dhillon, a British-Born Medical Oncologist of Indian Origin, the Pioneer of Recent Innovation of Bowel Cancer Vaccine: A Medicometric Portrait - Koley, Susanta (Journal of Data Science, Informetrics, and Citation Studies)
Dr. Perminder Tony Singh Dhillon, popularly known as Dr. Tony Dhillon, is a celebrated medical oncologist and pioneer of recently (first) developed bowel cancer vaccine, under whose headship groundbreaking global trial of the vaccine is going on. This medicometric study covers his 29 publications during 2003-2023 with 269 co-authors. He has one single authored and 28 multi-authored paper. His highest number of publication is 6 in 2005. Using his biographical data and bibliographic-information, this study draws a short life history and journey of the Britain-born medical scientist of Indian origin (Punjab) in cancer research and identifies his year wise growth of research publications, authorship patterns, author productivity, research team and co-authors, leading collaborative authors, scattering of publications in several communication channels. His most notable journal is Journal of Clinical Oncology, a high impact UK journal for his paper publication. In all, degree of collaboration is 0.96. It counts Citation Growth Rate according to citation received in different Abstracting and Indexing Journals (GS, PM and RG) including citation analysis, Citation received patter, Relative Un-cited Index (RUI) and Relative Citation Impact (RCI), etc. The RUI values for the study period ranged from 0.01 to 0.03 in three databases. The highest RCI value is 2.74 in RG in 2006. Among highest frequency keywords, Colorectal (Colon+rectum) cancer, that is, bowel cancer, the prime theme of this study along with other nine has been appeared 3 times each. It also examines whether the data set follows Lotka’s Law and Bradford’s Law or not.
Keywords: Perminder Tony Singh Dhillon; Biobibliometric; Medicometric; Citation Growth Rate; Citation Relative Impact; Relative un-cited index; Tony Dhillon; Punjab; Bowel cancer; Colorectal Cancer; Bowel cancer vaccine; Surrey University (UK).